2009
DOI: 10.2353/ajpath.2009.081067
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV) Infection of Human Macrophages Is Increased by Dopamine

Abstract: The prevalence of human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) that result from HIV infection of the central nervous system is increasing. Macrophages, the primary target for HIV within the central nervous system, play a central role in HIV-induced neuropathogenesis. Drug abuse exacerbates HAND, but the mechanism(s) by which this increased neuropathology results in more severe forms of HAND in HIV-infected drug abusers is unclear. The addictive and reinforcing effects of many d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
130
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 72 publications
(77 reference statements)
6
130
1
Order By: Relevance
“…A few investigators have used in vitro studies investigating the role of dopamine in HIV replication using lymphocytes or macrophages [18,41,42]. In an early study, Rohr et al [41] showed that dopamine (100 μM) stimulated HIV-1 transcription and replication (p24 antigen) in Jurkat T cells (T lymphocytes) and in peripheral blood mononuclear cells (PBMC).…”
Section: Dopamine and Hiv Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A few investigators have used in vitro studies investigating the role of dopamine in HIV replication using lymphocytes or macrophages [18,41,42]. In an early study, Rohr et al [41] showed that dopamine (100 μM) stimulated HIV-1 transcription and replication (p24 antigen) in Jurkat T cells (T lymphocytes) and in peripheral blood mononuclear cells (PBMC).…”
Section: Dopamine and Hiv Replicationmentioning
confidence: 99%
“…Furthermore, exposure to most drugs of abuse increases brain levels of dopamine well beyond basal levels and levels associated with "natural rewards" (e.g., food, sex) [11][12][13][14][15]. Finally, dopamine has been implicated in HIV and simian immunodeficiency virus (SIV)-induced brain pathology [16,17], and shown to promote HIV replication in macrophages [18]. The purpose of this review is to evaluate the potential role of dopamine in the development of HAND/HAD and in the exacerbation of these conditions by drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Over production of NO has been suggested to also increase HIV-1 replication. HIV-1 infection not only causes an increase in ROS generation but also leads to depletion of protective antioxidants in particular, glutathione (138,144). Thus HIV disease is characterized by chronic oxidative stress which drives disease pathogenesis.…”
Section: Oxidative Stress In Hiv Infectionmentioning
confidence: 99%
“…Commonly abused substances like alcohol, the opioids, other sedatives, the stimulants, marijuana, or more exotic substances like hallucinogens, combinations, or socalled 'designer drugs,' synthetic cannabinoids, etc., have almost all been associated with either cognitive or neuronal dysfunction or laboratory-derived brain damage on mammals. [22][23][24][25][26][27][28][29][30][31].…”
Section: Cognitive Effects Of Drug Usementioning
confidence: 99%